Exploring Diverse Oral Pathologies among Various Breeds of Canines: A Review - Nidhi Kumari; Gargi Sarode; Urmi Ghone; Shambhavi Ganjave; Vini Mehta; Renuka Gophane; Sachin Sarode (The Indian Veterinary Journal, 2026)
The paper summarizes the existing state of knowledge, which provides a resource for reviewing the oral pathologies in canines that may possibly be helpful in curative or analytical goals for human and veterinary medicine. It reviews the data of 462 cases that have been reported in 17 previously published articles. A search was conducted to identify appropriate papers from different databases (Google Scholar, PubMed, SCOPUS and Web of Science) and were analyzed for quality. In addition to this, outcome data were extracted in the form of graphs for summary. A high degree of heterogeneity was observed in the included studies regarding their inclusion and exclusion criteria, pathologies in different breeds, and the definition of survival. There is a need to standardize the reporting of diseases with appropriate treatment modalities. This present paper covers the various oral pathologies that may support the design of future studies.